Harry, a history : the true story of a boy wizard, his fans, and life inside the Harry Potter phenomenon - Anelli, Melissa (Pocket Books, 2008)
As webmistress of The Leaky Cauldron, one of the most popular Harry Potter sites on the Internet, Melissa Anelli had a front row seat to the Harry Potter phenomenon. Whether it was helping Scholastic stop leaks and track down counterfeiters, hosting live PotterCasts at bookstores across the country, touring with the wizard rock band Harry and the Potters, or traveling to Edinburgh to interview J. K. Rowling, Melissa was at the center of the Harry Potter tornado, and nothing about her life would ever be the same--Publisher description.